Effectiveness of Using Virtual Reality (VR) Technology in Learning English for Specific Purposes (ESP) for High School Students - Muhajir Muhajir; Ihramsari Akidah (Jurnal Pendidikan Bahasa Inggris Undiksha, 2026)
The low ability of high school students in mastering English for Specific Purposes (ESP) lessons is caused by the dominance of conventional methods that are theoretical and less contextual. The urgency lies in learning innovations that can improve students' language skills and learning motivation. The aim is to analyze the effectiveness of using VR in ESP learning, evaluating its influence on student motivation and learning outcomes. The research approach uses a quantitative quasi-experimental design. The sample is two high school classes, each consisting of 33 students. Data were collected through tests via pre-test and post-test, learning motivation questionnaires and observations. Data analysis techniques were carried out using normality tests, homogeneity, one-way ANOVA, effect size and Pearson correlation with the help of SPSS 29.0. The results showed a significant increase in the experimental group compared to the control group, with the average learning outcome increasing from 66.12 to 85.45 and learning motivation reaching an average of 84.76. The effect size values ​​of 2.47 and 2.17 for motivation indicate a very large influence. There is a strong positive correlation (r = 0.782) between motivation and learning outcomes. Conclusion: The use of VR significantly improves the effectiveness of ESP learning and student motivation. Implications: The impressive integration of technology into the English curriculum creates interactive, contextual, and relevant learning.